Insecticidal activities of Citrus aurantifolia essential oil against Aedes aegypti (Diptera: Culicidae) - Riju Sarma; Kamal Adhikari; Sudarshana Mahanta; Bulbuli Khanikor (Toxicology Reports, 2019)
Background: In the recent time, global attention for the control of vectors has shifted from chemical insecticides to botanicals. In the present investigation, authors attempted to evaluate the efficacy of peel and leaf essential oil (EO) of Citrus aurantifolia against Aedes aegypti. Results: The results revealed that both the oils possess more ovicidal activity (LC50 value of 5.26 ppm and 17.71 ppm for leaf and peel oil respectively at 72 h) than larvicidal activity. As larvicide, the essential oil from the peel of Citrus aurantifolia showed rapid effect with LC50 value of 128.81 ppm at 24 h which reduced to 106.77 ppm at 72 h while the leaf oil showed slow effect with LC50 value of 188.59 ppm, 107.37 ppm and 104.59 ppm at 24 h, 48 h and 72 h respectively. Again, the two essential oils did not show significant adulticidal activity. GC–MS analysis of both the oils recorded presence of different compounds. As a major constituent compound of the leaf EO of Citrus aurantifolia, citral was tested for their ovicidal, larvicidal and adulticidal activities against Aedes aegypti. The result showed highest ovicidal activities (LC50 value of 4.84 ppm at 72 h) of citral followed by larvicidal (LC50 value of 87.02 ppm at 24 h) and adulticidal (LC50 value of 103.88 ppm at 24 h) activities. Conclusion: From this study, it can be concluded that the essential oil extracted from the leaf and peel of Citrus aurantifolia and one of its major constituent compound citral can be included in the mosquito control programme of Aedes aegypti. Keywords: Citrus aurantifolia, Aedes aegypti, Citral